From Biological Control to Invasion: The Ladybird Harmonia Axyridis as a Model Species
DOI: 10.1007/978-1-4020-6939-0_16
|View full text |Cite
|
Sign up to set email alerts
|

Current and potential management strategies against Harmonia axyridis

Abstract: This paper reviews the current and potential methods to control the harlequin ladybird, Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae), an Asian predatory beetle invasive in Europe and the Americas where it has become a human nuisance, a grape and wine pest and a threat to native biodiversity. Current methods to manage this invasive species include: techniques to mechanically prevent adult beetles from entering buildings in autumn or to remove aggregates of beetles inside buildings, e.g. using various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…Nevertheless, an ectoparasitic mite (C. epilachnae) has been considered as a potential biological control agent of a phytophagous coccinellid (Schroder, 1982). Recently, an ectoparasitic mite (C. hippodamiae) has been identified that might aid in the suppression of populations of an invasive entomophagous coccinellid (H. axyridis) within an IPM framework (Kenis et al, 2008). A research program to address this proposition is needed but is complicated given the value of H. axyridis as an important predator of sternorrhynchan pests in agricultural landscapes and the low host specialization of the mite.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, an ectoparasitic mite (C. epilachnae) has been considered as a potential biological control agent of a phytophagous coccinellid (Schroder, 1982). Recently, an ectoparasitic mite (C. hippodamiae) has been identified that might aid in the suppression of populations of an invasive entomophagous coccinellid (H. axyridis) within an IPM framework (Kenis et al, 2008). A research program to address this proposition is needed but is complicated given the value of H. axyridis as an important predator of sternorrhynchan pests in agricultural landscapes and the low host specialization of the mite.…”
Section: Discussionmentioning
confidence: 99%
“…This mite also increased overwintering mortality of A. bipunctata males (Webberley and Hurst, 2002;Webberley et al, 2006). Recently, Kenis et al (2008) proposed the use of C. hippodamiae as a biocontrol agent within an integrated pest management program against the nuisance coccinellid, H. axyridis. Before this occurs, a risk assessment on the non-target implications of releasing this polyphagous mite seems warranted.…”
Section: Parasitic Mitesmentioning
confidence: 99%
See 2 more Smart Citations
“…Pupae may be victims of parasitoids that attack all coccinellid life stages, and some dipteran parasitoids, such as Phalacrotophora sp. (Diptera: Phoridae), are even late prepupal or pupal parasitoids specialists (Osawa, ; Hurt et al ., ; Kenis et al ., ; Riddick et al ., ). Ladybeetle pupae may also be preyed upon by conspecific ladybeetle larvae or by intraguild predators (Osawa, ; Hironori & Katsuhiro, ; Sakuratani et al ., ; Félix & Soares, ; Lucas, , ).…”
Section: Introductionmentioning
confidence: 99%